Implementasi Project Based Learning Mata Kuliah Aplikasi Komputer dalam Pengabdian Masyarakat - Siska Almaniar; Ilham Wahyu Pamungkas; Syerina Raihatul Jannah; Venny Agustin; Rahmawaty Hasibuan; Yuliansyah Yuliansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activityto aims to implement the Computer Applications course to enhance information technology literacy among the children of Hidayatullah Orphanage in Palembang. The program comprehensively introduces both hardware and software components of computers. Furthermore, the activities focus on knowledge transfer through interactive education to ensure participants acquire a solid understanding of technology and its effective utilization. The strategy employed to impart knowledge on computer applications includes socialization and hands-on practice with computer devices and relevant applications for the children at the orphanage. Through this initiative, the children, particularly students, gain valuable opportunities to build a strong foundation in digital skills, equipping them to navigate the rapid advancements of information technology in the modern era.